SIMULATION SERVICE PROVIDING IN A DISTRIBUTED SIMULATION ENVIRONMENT - Cheptsov, Alexey (International Journal of Computing, 2014)
Simulation of complex dynamic systems is an interdisciplinary problem. To solve this problem the author suggests a distributed simulation environment as a new form of simulation means system organization that provides web-based distributed simulation of engineering and industrial tasks as simulation services using Discrete Event Simulation Framework on the basis of Grid infrastructure. The Unified Process of Simulation Services Development based on Unified Modeling Language is proposed.